2022
DOI: 10.1186/s12879-022-07118-7
|View full text |Cite
|
Sign up to set email alerts
|

Early clinical and microbiological predictors of outcome in hospitalized patients with cryptococcal meningitis

Abstract: Background Cryptococcal meningitis causes high mortality in immunocompromised and immunocompetent patients. The objective of this study was to identify early predictors of clinical outcome, available at the first days of hospitalization, in patients with cryptococcal meningitis in a tertiary center in Brazil. Methods Ninety-six cases of cryptococcal meningitis with clinical, epidemiological and laboratory data, and identification and antifungal sus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 105 publications
0
6
0
Order By: Relevance
“…In an early study, 88 patients with CM were identified, and 37 (42%) were HIV-infected; they found patients who died had significantly lower CSF WBC, but this study contained HIV-positive patients, whom themselves had lower CSF WBC than HIV-negative patients [ 22 ]. In a recent study, early clinical and microbiological predictors of outcome in hospitalized patients with CM were evaluated [ 23 ], and older age and quantitative CSF yeast counts performed by direct microscopic exam were associated with mortality in multiple analyses by logistic regression [ 23 ]. We also found that male gender was significantly associated with mortality.…”
Section: Discussionmentioning
confidence: 99%
“…In an early study, 88 patients with CM were identified, and 37 (42%) were HIV-infected; they found patients who died had significantly lower CSF WBC, but this study contained HIV-positive patients, whom themselves had lower CSF WBC than HIV-negative patients [ 22 ]. In a recent study, early clinical and microbiological predictors of outcome in hospitalized patients with CM were evaluated [ 23 ], and older age and quantitative CSF yeast counts performed by direct microscopic exam were associated with mortality in multiple analyses by logistic regression [ 23 ]. We also found that male gender was significantly associated with mortality.…”
Section: Discussionmentioning
confidence: 99%
“…However, no overall survival benefits were observed through CrAg screening [ 37 ], except for patients with CrAg titers ≥1:160, who had 2.6-fold higher 6-month mortality compared to patients with titers <1:160 [ 35 ]. Other laboratory tests such as quantitative CSF yeast count and clearance, CSF cytokines, CSF white cell count, and antifungal susceptibility have been reported in several studies to affect hospital outcomes [ 38 41 ]. These factors were not evaluated in this study because they were not routinely available for clinical care in this setting.…”
Section: Discussionmentioning
confidence: 99%
“…Fungal burden has been associated with mortality in CM patients [17,[30][31][32][33][34]. However, fungal burden is formally evaluated with quantitative CSF cultures, but this methodology is usually unavailable in routine clinical practice in some low-and middle-income countries due to limited laboratory conditions [30,35]. Above all, cryptococcal culture of CSF samples often turns negative after CM early treatment but is not re ective of the therapeutic effect of CM [36].…”
Section: Discussionmentioning
confidence: 99%
“…The baseline CSF cryptococcal count was the most valuable predictor for prognosis in our prediction model. Some studies also indicated that the baseline CSF cryptococcal count could be used to predict outcome in CM patients [14,35,[37][38][39]. A previous study showed that the CSF cryptococcal count decreased rapidly in the early stage of treatment, while the cryptococcal count tended to stabilize after 2 weeks of treatment [32].…”
Section: Discussionmentioning
confidence: 99%